Evaluation Of Character Education Of El-Fash Islamic Elementary School With Cipp Model - Damanik, Sudarman (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This research aims to determine the evaluation of basic level character education (independent, creative, useful, and honed spiritual aspects) in class III students at El-Fash Islamic Elementary School, South Tangerang City. This research was conducted using a descriptive qualitative approach where questionnaires by parents, documentation and portfolios were used as research instruments. Researchers have the assumption that a value can be called a character that is inherent in students if this value is also applied outside of school so that it becomes a habit. So this assumption will be assessed through a parent questionnaire regarding student habits outside of school. Evaluations produced using the CIPP (Context, Input, Process, Product) method are used to determine whether a program should be replaced, revised or stopped. The use of the CIPP model helps researchers in formulating revisions and matters related to the success or failure of a learning program. The average character score (independent, creative, useful, honed spiritual aspects) based on the vision and mission of El-Fash Islamic Elementary School is 2.0 on a scale of 0-3 (quite effective). Meanwhile, based on the scores from the 2010 Ministry of National Education character aspects, the character education of El-Fash Islamic Elementary School has met all the criteria in question. Therefore, researchers assess that El-Fash Islamic Elementary School has succeeded in carrying out its vision and mission with character and life skills education programs that have been implemented at the elementary level.